Effects of high night temperature on soybean yield and compositions - Yang, Lin; Song, Wenwen; Xu, Cailong; Sapey, Enoch; Jiang, Dong; Wu, Cunxiang (Frontiers in Plant Science, 2023)
We investigated the effects of high night temperatures on soybean yield formation and the dynamic changes of non-structural carbohydrates (NSC) during the seed filling period (R5-R7). Three types of soybeans were tested at night temperatures of 18°C and 28°C. The results revealed that high night temperatures induced smaller seed size, lower seed weight, and a reduced number of effective pods and seeds per plant, and thus, a significant reduction in yield per plant. The proportion of significant residues, primarily carbohydrates, was reduced under the high temperatures, suggesting that carbohydrates are more substantially effected by high night temperatures. Analysis of the relationship between the yield and the accumulation of NSC at the different temperatures shows that the ineffective yield of soybeans may be caused by excessive consumption of NSC’s photosynthetic assimilates. This study provides a theoretical basis for revealing the soybean's physiological and biochemical regulation mechanism in response to climate change. It reveals transcriptional adaptation under high night temperatures during the soybean seed filling stage and may identify a mechanism of selection by the expression of seed yield formation, providing strategies for future breeding practice. It also lays a foundation for formulating crop management strategies under future climate change scenarios.